PENERAPAN TEKNOLOGI DIGITAL DALAM PENGELOLAAN DANA PENDIDIKAN: PELUANG DAN TANTANGAN - Rajagukguk, Handyka Oktra; Ahmad, Masduki; Rochimah, Heni (Jurnal Manajemen Pendidikan, 2025)
The success rate of BOS fund implementation over the past three years shows great potential to continue to drive innovation in education management. Digital technology, with its various benefits, not only increases efficiency but also ensures equity in education across regions. This study analyzes the application of digital technology in education fund management in Indonesia, focusing on the allocation of School Operational Assistance (BOS) and its impact on efficiency, transparency, and equitable access to education. Data were collected through literature studies, government policy analysis, and interviews with school principals and financial staff in various regions. The results of the study show that the use of digital systems accelerates financial administration and supervision, and supports the optimization of fund allocation, especially in the 3T regions. The implications of this study are the need for improved digital infrastructure and ongoing training to expand the benefits of technology in education fund management nationally.